The “Palliative Soul”: Music Therapy, End of Life Care, and Humanizing the Patient - Tao, Zoe (Voices: A World Forum for Music Therapy, 2019)
This qualitative research project features semi-structured interviews on perspectives of humanistic care with Spanish physicians and therapists who have worked in or are familiar with music therapy and end of life care, disciplines that identify themselves as centering humanistic values in patient care. The purpose of the study was to have the thirteen music therapists and physicians elaborate on their perceptions regarding humanistic patient care and synthesize common elements from their interviews. A grounded theory approach was used to construct and derive themes among interviewees, and a narrative method of analysis was used to highlight salient philosophies of care and moments of conversation with clinicians. Building off of the interviews, this article explores how artistic engagement in end-of-life contexts sets up avenues for spiritual, psychosocial, and medical care. This “palliative soul” approach to patient care illuminates how health professionals may humanize patients at the end of life: leaning in to experiences of suffering with intention and an open ear, approaching patients in anticipation of their potential spiritual, emotional, and psychosocial needs, defining suffering, wellbeing, and effective clinical intervention through the patient’s voice, thinking actively about their own biases and shortcomings in care, and overall seeing the beauty and humanity in people both within and despite their arrival at end-stage disease. Lastly, this article discusses how even outside the context of end of life care, health professionals may broadly adopt the “palliative soul” and incorporate the needs of patients and their relational networks into clinical practice.